Hand Gesture for Controlling a Robotic Device using a Personal Computer (International Journal of Engineering and Computer Science, 2014)
In the field of IMAGE PROCESSING hand gesture recognition is one of the most interesting and challenging genre. Gesture recognition is basically a non-verbal way of communication. Under this title, we will be basically developing a system which recognizes human hand gestures performed in front of the personal computer and uses this gesture for performing movement of a robotic car placed in the vicinity. In this paper web camera is used, after the grabbing of  the image we subject the  image to image processing algorithms like gray scaling, thresholding , blur, blob detection, segmentation and finally vector calculation. The system will use a single, color camera mounted above a neutral colored desk surface next to the computer. The paper briefly describes the schemes of capturing the image from web camera, image detection, processing the image to recognize the gestures as well as few results. This approach can be implemented in real time system very easily.